Velocity & displacement-dependent damper: A novel passive shock absorber inspired by the semi-active control. (15th January 2018) - Nie, Shida; Zhuang, Ye; Wang, Yong; Guo, Konghui
Highlights: A velocity & displacement-dependent damper which realizes semi-active control with novel mechanical structure is proposed. The results show that the novel damper can perform as good as a semi-active control damper. No add-on hardware or energy consumption is needed for the novel damper to achieve the remarkable performance. Abstract: The performance of velocity & displacement-dependent damper (VDD), inspired by the semi-active control, is analyzed. The main differences among passive, displacement-dependent and semi-active dampers are compared on their damping properties. Valve assemblies of VDD are modelled to get an insight into its working principle. The mechanical structure composed by four valve assemblies helps to enable VDD to approach the performance by those semi-active control dampers. The valve structure parameters are determined by the suggested two-step process. Hydraulic model of the damper is built with AMEsim. Simulation result of F-V curves, which is similar to those of semi-active control damper, demonstrates that VDD could achieve the similar performance of semi-active control damper. The performance of a quarter vehicle model employing VDD is analyzed and compared with semi-active suspension. Simulation results show that VDD could perform as good as a semi-active control damper. In addition, no add-on hardware or energy consumption is needed for VDD to achieve the remarkable performance.